Learning Music Using Pianika Application Instruments to Improve the Musical Skills of Children with Disabilities - Anggraeni, Nurlita; Kartikasari, Ratna Indah; Wijayanto, Wasis (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
Introduction/Main Objectives: This study aims to describe the process of learning music arts using the pianica application instrument and its impact on the musical skills of mentally retarded children at SLB Negeri Purwosari. Research Methods: The approach used is qualitative with a case study type. Data collection techniques are carried out through direct observation of classroom learning activities, in-depth interviews with teachers and students, and documentation including photos, videos, and learning notes. Finding/Results: The results of the study indicate that the use of the pianica application as a learning medium can significantly increase the interest, focus, and musical skills of mentally retarded children. Children look more enthusiastic when participating in learning, show active participation, and are able to follow instructions better. In addition, the interaction between teachers and students runs more effectively so that the learning process becomes more enjoyable and conducive. Teachers can easily deliver music material and adjust it to the needs of each student. Conclusion: This study provides an overview that application-based digital learning media can be an effective alternative in learning music arts for children with special needs, especially mentally retarded children. The use of the pianica application not only makes it easier for students to recognize notes and rhythms, but also helps increase their self-confidence. Thus, application-based digital media has been proven to provide a positive contribution to the achievement of learning outcomes for mentally retarded students in the field of musical arts.